MANIFESTAÇÕES ORAIS EM PROFISSIONAIS DA SAÚDE BUCAL ACOMETIDOS POR COVID- 19 ENTRE OS ANOS DE 2020/2022 - Daniela Brostolin da Costa (2024)
COVID-19 presents variable clinical presentations and among the various signs and symptoms described in the literature, there is evidence of a positive association between numerous oral manifestations and the disease, such as taste alterations, xerostomia, mucosal lesions, among others. This study aimed to describe the occurrence and clinical evolution of oral manifestations in oral health professionals affected by COVID-19 and to identify and explore individual characterization variables, occupational variables, related to COVID-19 and the association of oral manifestations due to the disease. The proposed methodology was a cross-sectional study. The target population of the study were oral health professionals from the permanent staff of the Municipal Health Department of Campo Grande, MS (SESAU). Data collection was carried out in 3 stages – (1) admission and screening of participants, (2) formation of study groups and (3) monitoring of participants with persistent oral manifestations through 2 self-reported questionnaires via the Google Forms platform. The results were presented in tabular format, consisting of absolute and relative frequencies. Considering the results obtained in this survey of 239 oral health professionals, 58.6% (95% CI: 52.1%-64.9%) were affected by COVID-19. Of these, 42.1% (95% CI: 34.0%-50.3%) reported the occurrence of oral manifestations, mainly in the first episode of COVID-19. The most frequent types of manifestations were: change/lack of taste, xerostomia, difficulty swallowing food and halitosis, with a predominance of onset between the 1st and 7th day after the onset of other symptoms, and complete remission within 15 days of their onset. Regarding long COVID, change in taste and xerostomia were the most prevalent persistent post-COVID symptoms with complete remission predominantly greater than 5 months after diagnosis. There was no difference in the percentage of cases of oral manifestations due to COVID-19 in the variables: sex, age group, color/race, professional category, presence of health problem and/or comorbidities, smoking, alcohol consumption, number of doses of vaccine against COVID-19 administered. Based on the results of this research, we can conclude that the prevalence of COVID-19 in oral health professionals who are members of the municipal public servants of Campo Grande - MS was higher than what is indicated as scientific evidence. Regarding oral manifestations associated with COVID-19, this research was consistent with other studies, both in the occurrence and in the most prevalent types of manifestations: change/lack of taste and xerostomia, including in long-term COVID. Given the above, it is clear that there is a need for a multidisciplinary approach in the monitoring of patients with COVID-19, in which the presence of an oral health professional is mandatory.